Desenvolvimento de filmes nanocompósitos contendo purê de vegetais para aplicação como embalagem comestível - Lorevice, Marcos Vinicius (Universidade Federal de São Carlos, 2015)
Petroleumderived packaging are neither renewable nor biodegradable. Based on it, recent studies have been focused in biopolymer-based packaging, such as in polysaccharides (e.g., pectin and chitosan), due to their good renewable and biodegradable characteristics. However, their physical-chemical properties (mechanical, thermal, and barrier) are urged to be improved. The addition of nanoparticles (NPS) as reinforcing agents has been shown as a feasible means of improving such properties. The goal of this work was the development of pectin (PEC) (low and high methoxyl degree, MD)-based nanocomposite films incorporated with chitosan (CS) and poly(ε-caprolactone) (PCL) nanoparticles (CSNP and PCLNP, respectively). CSNP were obtained by ionotropic gelation whereas PCLNP were obtained by the nanoprecipitation method. All NPS were characterized as to their morphology, size, and zeta potential. The CSNP size was nearly 100 nm and their zeta potential was close to + 20 mV, results which are in agreement whit CS cationic properties and indicated good suspension stability. PCLNP presented size values near to 130 nm and zeta potential of approximately - 20 mV because the surfactant is spread over PCLNP surface. PCLNP showed a smaller polydispersity index than CSNP, indicating a more homogenous suspension. This was also observed through electron microscopy of PCLNP. The nanocomposite films were obtained by casting from PEC/NPS film-forming solutions. The nanocomposite films’ mechanical, thermal, and water barrier properties were studied. The MD did not affect the analyzed properties of PECbased films. The addition of NPS (CSNP and PCLNP) increased the tensile strength and degradation temperature of all PEC-based films, suggesting good interactions between PEC network and NPS surface. The addition of PCLNP to low MD PEC films improved the tensile strength in more than 100%. Although, NPS did not change the water vapor permeability of the PEC-based nanocomposite films, which could be related with PEC good water solubility and NPS affinity to water molecules. These results indicate a novel material with physical-chemical properties desirable for food packaging applications, making this product competitive when compared with petroleum-based packaging.
Development of vegetable puree-containing nanocomposite films for edible food packaging
Keywords: Filmes; Nanopartículas; Quitosana; Pectina; Poliepsloncaprolactona; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA ORGANICA::FISICO-QUIMICA ORGANICA